Flight of San Jose scale, Quadraspidiotus perniciosus males and time of crawler appearance in orchards of northern Greece - Kyparissoudas, D.S. (ENTOMOLOGIA HELLENICA, 1987)
The seasonal flight of San Jose scale (SJS), Quadraspidiotus perniciosus Comstock, males was studied during 1984-1987 in peach and nectarine orchards, under two different climatic conditions in Central Macedonia (Northern Greece), using sex pheromone traps. In late-season regions there were three periods of male flight activity (May, July-August, September – October), while in early-season regions there was also a partial fourth one (mid April-May, mid June-July. August – mid September and late September – early November). In the latter regions these flights can be correlated with the appearance of the scale crawlers during three periods (late May – early July, mid July – August, September – October) and a partial fourth one (November) in milder years, as determined using the sticky-tape trap technique. Pheromone traps and sticky-tape traps can be used for the study of phenology of San Jose scale, under conditions prevailing in Northern Greece.